Comparison of Interrupted Vs Continuous Suture Urethroplasty in Tabularised Incised Plate Hypospadias Repair. A Prospective Study - Rafiq, Hafiza Mariam; Bashir, Muhammad Kashif; Yousaf, Abdullah; Aman, Nadir; Noor ul Haq, Mahwish; Khaliq Siddiqi, Umair (Indus Journal of Bioscience Research, 2024)
objectives: Hypospadias, a congenital malformation characterized by the abnormal positioning of the urethral opening, poses a significant challenge for paediatric urologists. Tabularised incised plate urethroplasty (TIPU) is a widely accepted surgical approach, offering reliable function and cosmetic outcomes. While the overall technique remains consistent, the choice between continuous and interrupted suture closure of the urethral plate remains a point of debate. This prospective study aims to compare these two suturing methods in TIP urethroplasty, focusing on key outcomes such as fistula formation, meatal stenosis, glans shape, urethral stricture, surgical site infection and patient satisfaction. Methods: This prospective study aimed to evaluate the outcome of tubularized incised plate urethroplasty (TIP) conducted at the Paediatric Surgery Department of Mayo Hospital Lahore/KEMU, involving 60 paediatric patients with primary sub coronal, distal and mid penile hypospadias from December 2023 to August 2024 who were randomized in two groups: Group A (30) boys received interrupted suture repair and Group B (30) boys received continuous suture repair . Outcomes were assessed through follow-up visits focusing on post-op complication rate and cosmetic appearance. Results: This study found interrupted suture technique superior to continuous suture technique in term of better functional and cosmetic outcome and fewer post operative complication. Patient and parent satisfaction were also found higher in interrupted suture. Post operative complications were most common in continuous group (mean=0.77) compared to the interrupted group (mean=0.20). the former group also had higher fistula rate (mean=0.90 vs 0.50) For other post operative outcomes, continuous group also shows slightly higher rate but had a better cosmetic appearance than the interrupted group (mean=0.27 vs 0.03)